The role of DC-SIGN as a trans-receptor in infection by MERS-CoV - Labiod, Nuria; Luczkowiak, Joanna; Tapia, María M.; Lasala, Fátima; Delgado, Rafael (Frontiers in Cellular and Infection Microbiology, 2023)
DC-SIGN is a C-type lectin expressed in myeloid cells such as immature dendritic cells and macrophages. Through glycan recognition in viral envelope glycoproteins, DC-SIGN has been shown to act as a receptor for a number of viral agents such as HIV, Ebola virus, SARS-CoV, and SARS-CoV-2. Using a system of Vesicular Stomatitis Virus pseudotyped with MERS-CoV spike protein, here, we show that DC-SIGN is partially responsible for MERS-CoV infection of dendritic cells and that DC-SIGN efficiently mediates trans-infection of MERS-CoV from dendritic cells to susceptible cells, indicating a potential role of DC-SIGN in MERS-CoV dissemination and pathogenesis.